2020
DOI: 10.1002/adhm.202001271
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pathways for Pathological Calcification in the Human Body

Abstract: Biomineralization of skeletal components (e.g., bone and teeth) is generally accepted to occur under strict cellular regulation, leading to mineral–organic composites with hierarchical structures and properties optimized for their designated function. Such cellular regulation includes promoting mineralization at desired sites as well as inhibiting mineralization in soft tissues and other undesirable locations. In contrast, pathological mineralization, with potentially harmful health effects, can occur as a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 362 publications
(735 reference statements)
0
57
0
1
Order By: Relevance
“…Arterial calcification is also described in OPN deficiency or hypophosphorylation [ 116 ]. However, tumor microcalcifications in the form of hydroxyapatite have also been associated with high OPN expression, without a known mechanism [ 117 , 118 ]. These contradictory actions stress the need to study sortilin 1 and OPN phosphorylation states in soft tissues, including the brain, which has high expression of OPN and sortilin 1, to elucidate the ectopic calcifications observed in RS.…”
Section: Fam20c Biological Functions In Non-mineralized Tissuesmentioning
confidence: 99%
“…Arterial calcification is also described in OPN deficiency or hypophosphorylation [ 116 ]. However, tumor microcalcifications in the form of hydroxyapatite have also been associated with high OPN expression, without a known mechanism [ 117 , 118 ]. These contradictory actions stress the need to study sortilin 1 and OPN phosphorylation states in soft tissues, including the brain, which has high expression of OPN and sortilin 1, to elucidate the ectopic calcifications observed in RS.…”
Section: Fam20c Biological Functions In Non-mineralized Tissuesmentioning
confidence: 99%
“…[ 75 ] Breast MCs are calcium mineral deposits in breast tissue that are an important screening tool for diagnosis of benign or malignant breast cancer. [ 76 ] Studies showed the morpgology of MC can be related to the aggressiveness of the tumor, for example, casting‐type MCs are reported in aggressive tumor pathology compared to crushed stone (pleomorphic) or powdery. [ 75,76 ] The overexpression of human epidermal growth factor receptor type 2 (HER‐2) is highly associated with the occurrence of MCs in premalignant breast lesions, which can be an indicator of aggressive tumor growth.…”
Section: Phase Composition and Structural Analysismentioning
confidence: 99%
“…[ 76 ] Studies showed the morpgology of MC can be related to the aggressiveness of the tumor, for example, casting‐type MCs are reported in aggressive tumor pathology compared to crushed stone (pleomorphic) or powdery. [ 75,76 ] The overexpression of human epidermal growth factor receptor type 2 (HER‐2) is highly associated with the occurrence of MCs in premalignant breast lesions, which can be an indicator of aggressive tumor growth. [ 75,77 ] The relationship of MCs and breast cancer prognosis is not clear yet.…”
Section: Phase Composition and Structural Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Microcrystalline pathology is an exciting research field [1][2][3][4][5][6][7][8][9][10] in which most investigations have been performed on the mineral component of the biological deposits induced by the pathology. With respect to urolithiasis, the morphoconstitutional model defines the morphology of the kidney stones as one of the key parameters to establish a link between the At the mesoscopic scale, the morphology and size of crystallites can be determined by scanning electron microscopy (SEM) [6,20,21], while at the nanometric scale, the size of crystals is determined by X-ray scattering [22][23][24], powder neutron diffraction (PND) [25,26], X-ray absorption spectroscopy [27][28][29][30][31] or by transmission electron microscopy [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%